HR practices, knowledge sharing and protection activities, and performance - a moderation model - Gomes, Jorge FS (2017)
Innovation and HRM practices are connected, but the nature of these linkages may not be completely understood. Practical examples where knowledge securing practices limit efficiency of creative work, and where rewarding established ways of work prevent new approaches from being tried, suggest that there are challenges. In this study, we examine the relationships between different forms of HRM practices, knowledge sharing and protection (i.e., knowledge activities), and performance outcomes. Our findings from empirical analysis among 150 firms suggest that HRM practices are positively related to subjective overall performance and innovation performance, and that knowledge sharing likewise has such a relationship with performance outcomes. Furthermore, when knowledge sharing is accompanied with HR practices targeted to securing knowledge, innovation performance can be improved. Knowledge securing also comes in play when it is combined with HR practices of personnel compensation and appraisal; in this case subjective performance is diminished. This leads us to suggest that companies might benefit from smart HRM systems